STRATEGI KOMUNIKASI PEMASARAN MATAYA ART AND HERITAGE PADA EVENT “PAMERAN KAIN NUSANTARA’’ - Deky Seto Aji; Musta’an Musta’an (JURNAL ILMIAH EDUNOMIKA, 2021)
This research is a case study because this research uses a qualitative approach and involves case study research. The result of this research is descriptive analysis. Sources of data in this study are words and actions obtained from informants connected to research, while documents or other written sources are additional data. The data analysis technique used interactive analysis. Analysis was carried out on all data obtained from interviews and documentation. The results ofthe research include History of the establishment of Mataya Arts And Heritage, Organizational Structure of Mataya Arts And Heritage, Management of Mataya Arts And Heritage, Vision and Mission of Mataya Arts And Heritage, Cultural Event Activities " Cerita Kain tentang Kain " / Kain Nusantara Surakarta Held by Mataya Arts And Heritage, Marketing Communication Strategy with the "Friendship" Principle, Communication strategy to increase customer trust, Strategyfor selecting promotional media in the Mataya Arts And HeritageEvent Organizer. The conclusion of this research is the marketing communication strategy carried out by Mataya Art And Heritage at theKain Nusantara Event in Surakarta, and the social media used "Mataya Art And Heritage". Keywords: strategy, communication, case studies, descriptive analysis, interactive analysis